1995
DOI: 10.1007/bf00187888
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic retrograde cholangiographic demonstration of a double gallbladder following laparoscopic cholecystectomy

Abstract: We report a case of a doubled gallbladder missed in preoperative ultrasound and laparoscopic cholecystectomy but demonstrated by endoscopic retrograde cholangiography (ERC) postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…71 In fact, ultrasonography, which is ordinarily sufficient for preoperative investigation of gallbladder diseases, may fail to detect a second gallbladder due to the insensitivity of the test itself or misinterpretation of the findings. 72,73 Moreover, even the laparoscopic exploration of peritoneal cavity may produce the same disappointing result, 74 so that singlestaged successful laparoscopic removals of double gallbladders are rarely reported. 75,76 Either gallbladder may be stone-diseased 77 thus causing missing or, potentially, intentional sparing of one gallbladder in the course of laparotomic as well laparoscopic cholecystectomy, with subsequent possible complications or relapse of lithiasis 78 and the need of a second operation to remove the missed gallbladder.…”
Section: Discussionmentioning
confidence: 98%
“…71 In fact, ultrasonography, which is ordinarily sufficient for preoperative investigation of gallbladder diseases, may fail to detect a second gallbladder due to the insensitivity of the test itself or misinterpretation of the findings. 72,73 Moreover, even the laparoscopic exploration of peritoneal cavity may produce the same disappointing result, 74 so that singlestaged successful laparoscopic removals of double gallbladders are rarely reported. 75,76 Either gallbladder may be stone-diseased 77 thus causing missing or, potentially, intentional sparing of one gallbladder in the course of laparotomic as well laparoscopic cholecystectomy, with subsequent possible complications or relapse of lithiasis 78 and the need of a second operation to remove the missed gallbladder.…”
Section: Discussionmentioning
confidence: 98%
“…Another problem encountered in our observation was the partially intrahepatic location of the accessory gallbladder [2,7,10,11,26], which made the dissection from the liver parenchyma more difficult [10]. The intrahepatic location of an accessory gallbladder can lead to its being overlooked during surgery and to the need for a second cholecystectomy [10], as recently also reported following laparoscopic cholecystectomy [16]. In our observation, we found the argon-beam coagulator useful for achieving hemostasis during complete removal of the accessory gallbladder from the hepatic parenchyma of the right lobe of the liver.…”
Section: Discussionmentioning
confidence: 75%
“…In our observation, we found the argon-beam coagulator useful for achieving hemostasis during complete removal of the accessory gallbladder from the hepatic parenchyma of the right lobe of the liver. All reported cases of gallbladder duplication have been treated by open surgery, and only three cases of laparoscopic cholecystectomy have been reported [2,16,24]. To the best of our knowledge, therefore, this is the second case in which complete laparoscopic cholecystectomy was performed.…”
Section: Discussionmentioning
confidence: 85%
“…It has been suggested that ERCP is the most accurate test in displaying the biliary tract anatomy of gallbladder duplications [14] , however ERCP is not indicated for most patients with biliary colic due to its invasive nature [11] . In the present case, even though ERCP was performed for evaluation of the biliary stricture, it did not identify the medial gallbladder with an obstructed cystic duct.…”
Section: Discussionmentioning
confidence: 99%